Crohn's Disease and Ulcerative Colitis : From Epidemiology and Immunobiology to a Rational Diagnostic and Therapeutic Approach - Baumgart, Daniel C. (Springer International Publishing : Imprint: Springer, 2017)
This new edition is a unique combined resource for physicians and scientists addressing the needs of both groups. In addition to stimulating exchange and collaboration and shortening the path between discovery and application of new knowledge, the book helps clinicians understand new therapeutic concepts from their origins. The volume serves as a comprehensive guide to the current diagnostic modalities, including enhanced imaging techniques such as MRI and CT enterography, virtual colonoscopy, ultrasound, and endomicroscopy, as well as conventional and complex immunomodulatory principles. The latest edition also includes revised chapters from the previous edition, as well as new chapters reflecting current developments in the field. Written by experts in their field, Crohn's Disease and Ulcerative Colitis: From Epidemiology and Immunobiology to a Rational Diagnostic and Therapeutic Approach, Second Edition is of great value to gastroenterologists, surgeons, internists, pediatricians and gynecologists trainees, as well as all those involved in Crohn's disease, ulcerative colitis, and related autoimmune disorders.